2006
DOI: 10.1093/eurheartj/ehl365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of recovery following combination left ventricular assist device (LVAD) support and pharmacologic therapy

Abstract: This data set represents the first description of signalling pathways associated with the functional recovery of end-stage human heart failure and the identification of new targets in the human heart that are modified by this combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 33 publications
1
77
1
4
Order By: Relevance
“…Recently, Hall et al 69 performed a microarray analysis of 6 paired human heart samples before and after a novel combination therapy of LVAD and a selective β2 agonist, clenbuterol. They found a significant association between recovery and the integrin signaling pathway, and identified several novel targets that included EPAC2, a guanine nucleotide exchange factor that binds to cAMP.…”
Section: Changes In the Gene Expression In The Failing Myocardium Aftmentioning
confidence: 99%
“…Recently, Hall et al 69 performed a microarray analysis of 6 paired human heart samples before and after a novel combination therapy of LVAD and a selective β2 agonist, clenbuterol. They found a significant association between recovery and the integrin signaling pathway, and identified several novel targets that included EPAC2, a guanine nucleotide exchange factor that binds to cAMP.…”
Section: Changes In the Gene Expression In The Failing Myocardium Aftmentioning
confidence: 99%
“…2, 3 The molecular and biochemical mechanisms potentially implicated in reverse remodeling after LVAD implant remain still incompletely understood. [4][5][6] Since an abnormal increase in metalloproteinases (MMP) activity and reduced expression of tissue inhibitors of MMP (TIMP) appear to be involved in the progression to overt HF, 7,8 the normalization of MMP/TIMP balance following LVAD implantation is considered one of the putative mechanisms of myocardial functional recovery. 4 Several studies have suggested that oxidative stress acts on MMP metabolism favoring progression of cardiac remodeling, 9, 10 by direct activation of the latent form of MMP, by CARUSO R et al…”
mentioning
confidence: 99%
“…47 This process has provided a unique opportunity to access myocardial tissue for gene expression analysis before and after reverse remodeling to identify mechanisms that are associated with improvement in left ventricular function with mechanical unloading. The reverse remodeling process appears to be associated with genes in the integrin pathway, 48 arginine metabolism, 49 and Wnt signaling, 50 whereas failure to recover function was associated with profibrotic genes such as TGFB1. 51 For patients with end-stage heart failure for whom left ventricular assist device support is not indicated or required, cardiac transplantation is sometimes an option.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%